Soil sampling and methods of analysis - Carter, Martin R. (CRC Press, 2008)
Carter and Gregorich, both affiliated with Agriculture and Agri-Food Canada, compile information on the potential and limitations of commonly used soil analytical and sampling methods. For this second edition, they add several chapters that serve as "primers," describing the overall principles and concepts behind a particular type or types of measurement. All of the chapters retained from the earlier edition have been modified and updated, and there are new chapters added to reflect new microbiological techniques and the burgeoning interest in soil ecology. Other new chapters describe tools for characterizing the dynamics and chemistry of soil organic matter. A new section presents field- and lab-based methods for characterizing saturated and unsaturated soil hydraulic properties.